MSME AI Readiness Analysis Using The AIRI Framework: Analisis Kesiapan AI UMKM Menggunakan Kerangka Kerja AIRI - Muhammad Husein Budiraharjo; Alva Hendi Muhammad; Kusnawi (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2024)
AI is expected to become one of the key technologies supporting the development of MSMEs, which represent a major pillar of Indonesia's economy. Successful adoption and implementation of AI require the right strategies, one of which stems from an analysis of a company’s AI readiness. In this study, an AI readiness analysis was conducted using the AIRI framework on six MSMEs from various business sectors. The results of the analysis provided the AI readiness levels of each MSME, along with comparisons to similar industries and to industries of comparable business scale (MSME). The analysis also yielded several recommendations for AI adoption and strategies to enhance the AI readiness of each MSME. All the MSMEs involved in the study positively accepted the AI readiness analysis and the adoption recommendations provided. The study did not produce any feedback for improvements to the AIRI framework itself; however, there were suggestions for further development of the AIRI application to better assist MSMEs in determining AI readiness targets and appropriate AI implementation strategies in the future..